Placental Chorioangioma: A Case Report and Literature Review - Eserdağ, Süleyman; Zergeroğlu, Sema; Mollamahmutoğlu, Leyla; Zülfikaroğlu, Ebru; Mungan, Tamer; Danışman, Nuri (Gynecology Obstetrics & Reproductive Medicine, 2006)
When placental masses are discovered during routine conventional sonographic examination, differentiation between chorioangiomas and other lesions is not always possible. Absolute identification should be done prenatally by color flow mapping for every suspected placental mass. Because unidentif ied large chorioangiomas can cause more tragic perinatal complications compared to other placental lesions.